2021
DOI: 10.3892/mmr.2021.12071
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑29‑3p regulates the β‑catenin pathway by targeting IGF1 to inhibit the proliferation of prolactinoma cells

Abstract: The present study aimed to analyze the effects and underlying mechanisms of microRNA (miR)-29-3p on the proliferation and secretory abilities of prolactinoma cells by targeting insulin-like growth factor (IGF)-1/β-catenin. The relationship between miR-29a-3p and the survival of prolactinoma cells was analyzed with the Kaplan-Meier method in reference to The Cancer Genome Atlas. The expression levels of miR-29a-3p and IGF-1 in MMQ and GH3 cells were detected. A dual-luciferase reporter gene assay was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Intriguingly, we found that miR‐29c dramatically reduced the expression level of IGF1 among five candidate mRNAs in goat myoblasts (Figure S5C, p < .01). Correspondingly, knockdown and overexpression of circUSP13 significantly decreased and increased the expression of IGF1 (Figure S5D,E, p < .01, respectively), a well‐established regulator of myoblasts proliferation and differentiation 26,27 . Based on these findings, IGF1 could be considered as a potential target gene for miR‐29c in goat myogenesis.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…Intriguingly, we found that miR‐29c dramatically reduced the expression level of IGF1 among five candidate mRNAs in goat myoblasts (Figure S5C, p < .01). Correspondingly, knockdown and overexpression of circUSP13 significantly decreased and increased the expression of IGF1 (Figure S5D,E, p < .01, respectively), a well‐established regulator of myoblasts proliferation and differentiation 26,27 . Based on these findings, IGF1 could be considered as a potential target gene for miR‐29c in goat myogenesis.…”
Section: Resultsmentioning
confidence: 72%
“…IGF1 is an insulin-related peptide that stimulates both proliferation and differentiation of myocytes during myogenesis. 26,27,45 IGF1 regulates myostatin transcription by activating the transcription of nuclear factor of activated T-cells (NFAT) in an IP3/calcium-dependent manner and IGF-1 signaling via the activation of the PI3K/Akt pathway has been well characterized. 46,47 Moreover, inhibiting the IGF1/PI3K/AKT signaling pathway during the differentiation phase of myoblasts impeded the muscle-specific gene expression, preventing satellite cell fusion into myotubes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Downregulated miR-29a-3p might account for the tumor promotion of the lncRNA KCNQ1OT1 in hepatocellular carcinoma [30]. In addition, miR-29a-3p was also shown to inhibit the proliferative ability of prolactinoma cells via modulating the β-catenin signaling pathway [31]. Although the oncogenic role of this miRNA in laryngocarcinoma has been reported, its deliver from hBMSCs and the complex mechanisms remains unclear.…”
Section: Discussionmentioning
confidence: 99%